The Situation of the Assyrians in the Middle East in Period World War I - Letko, Paweł (Studia Warmińskie, 2019)
Assyrians are one of the least known ancient Christian communities in the Middle East. In the years 1914-1918, the Turkish authorities, with the participation of Kurds, began mass deportations and physical liquidation of Christians – Armenians, Greeks and Assyrians. Until recently, the Assyrians were the most forgotten victims of this crime. In the collective memory of the Assyrians, the years of the First World War were inscribed as seyfo, which means a sword in Aramaic language. The term seyfo functions as a synonym of the holocaust of Assyrian Christians. The article is an attempt to depict the genocide committed on the Assyrians in 1914-1918, taking into account the military and political background and the role played by world powers in the described events. It shouldn’t be forgotten that the basic reason for the extermination of the Assyrians was their religion and the fact that despite the threat of losing their lives, they did not want to give up. At the beginning of the First World War in the Ottoman Empire, Christians made up about 1/3 of the population. As a result of the events described, Christian-Muslim Turkey has become an entirely Muslim country.